IMPLEMENTASI KEBIJAKAN HIMBAUAN PENGANEKARAGAMAN KONSUMSI PANGAN DI BIDANG KETAHANAN PANGAN KOTA SUKABUMI - Meigawati, Dine; Melawati, Melawati (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2017)
This study aimed to analyze the implementation of policies call for diversification of food consumption in the Field of Food Security Sukabumi. In addition this study analyzes the factors that become supporters and obstacles in implementing it. These results indicate that the implementation of the policy of diversification of food consumption appeal has not been carried out effectively and efficiently. But the main factors that hinder the realization of this policy were in consumption patterns are always dependent on rice. Based on the analysis and discussion, the researchers conclude that the implementation of policies in the field of food appeal penganekaraaman Food Security Sukabumi is not operating effectively and efficiently